PERTIMBANGAN HAKIM MAHKAMAH AGUNG MEMUTUS KASASI TERDAKWA PERKARA KORUPSI PUTUSAN NOMOR 5190K/PID.SUS/2023 - Mahaldika Nilan Triwardani; Bambang Santoso (Sebelas Maret University, 2025)
This article analyzes the field of Criminal Procedure Law related to the considerations of the Justice in examining and deciding the cassation filed by the Defendant in a corruption case. The purpose of this article is to determine whether the justice's considerations in issuing a cassation decision in decision Number 5190K/Pid.Sus/2023 are in accordance with the provisions of the Criminal Procedure Code (KUHAP). The research method used is doctrinal or normative legal research. This research is prescriptive in nature which uses the collection of legal materials by means of literature study and the legal materials used are primary and secondary legal materials. Based on the results of the research, it can be concluded that the Supreme Court Judge (/justice?) has appropriately determined the cassation decision in the corruption case in decision Number 5190K/Pid.Sus/2023 because of the judge did not find any errors in the application of the law made by Judex Factie so that the Defendant is considered not to meet the requirements as stipulated in Article 253 paragraph (1) of the Criminal Procedure Code and states that the Defendant's cassation is rejected with revisions.